In vitro larval rearing method of eusocial bumblebee Bombus terrestris for toxicity test - Yuto Kato; Shingo Kikuta; Seth M. Barribeau; Maki N. Inoue (Scientific Reports, 2022)
Abstract Bumblebees are important pollinators of wild and agricultural plants but recently have been declining due to various stressors, such as pesticides and diseases. Because of the haplo-diploid sex determination system in hymenopterans, experiments using micro-colonies (small sub colonies without a queen) to identify risks to bumblebee health are limited as they are only able to produce males. Therefore, an experimental protocol for rearing bumblebee larvae in vitro is needed to better understand effects on worker larvae. Here, we aimed to establish a rearing method for larvae of Bombus terrestris for use in risk assessment assays. To confirm the validity of our rearing method, we tested two insecticides used for tomato cultivation, chlorfenapyr and dinotefuran. Bombus terrestris larvae fed with a high nutrient quantity and quality diet increased growth per day. All chlorfenapyr-exposed individuals died within 10 days at 2000-fold dilution, an application dose used for tomatoes. There were significant differences in adult emergence rate among almost all chlorfenapyr treatments. On the other hand, sublethal dinotefuran-exposure did not affect rates of pupation and adult emergence, growth, or larval and pupal periods. Although larvae were smaller than in the natural colony, this rearing method for B. terrestris larvae proved to be effective at evaluating realistic sub-colonies to pesticide exposures.